79. Status epileptics and myoclonus in comatose patients after cardiac arrest: To treat or not to treat. Issue 4 (April 2016) - Carrai, R.; Grippo, A.; Spalletti, M.; Scarpino, M.; Cossu, C.; Lanzo, G.; Peris, A.; Valente, S.; Amantini, A.
Abstract : Status epilepticus and myoclonus are common in comatose patients after cardiac arrest (Krumholz et al., 1988; Young et al., 1990). There is no consensus on when and for how long to treat this condition. This point became more relevant after introduction of therapeutic hypothermia (TH) because of some patients with MS treated with TH recovered consciousness (Rossetti et al., 2009). We propose a treatment protocol based on clinical-EEG features and somatosensory evoked potentials (SEPs) as prognostic indicator. In patients with absent SEPs we do not treat aggressively with AED considering the poor outcome. In patients with preserved SEPs we treat myoclonus if associated with GPEDs, convulsive status epilepticus and non convulsive status epilepticus (Beniczky et al., 2013). We use a combination of AED (valproate, levetiracetam) with sedation (propofol or midazolam). We present two representative cases in which we describe in more detail our therapeutic approach.